Valuation Of Convertible Loa.N Stocks On Kuala Lumpur Stock Exchange (KLSE) - Chong, Pak Kin (Universiti Sains Malaysia, 1995)
The research is a preliminary empirical study on the convertible loan stocks traded on the Kuala Lumpur Stock Exchange (KLSE) as there is a lack of such studies in the local market. The study aims to understand whether there exists any underpricing of convertible loan stocks as compared with a theoretical model.